Synthesis of Novel Porphyrin Derivatives and Investigate their Application in Sensitized Solar Cells - Jaafar, Mohammed Thamer; Ahmed, Luma Majeed; Haiwal, Rahman Tama (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
Solar energy has significant advantages compared to conventional sources such as coal and natural gas, including no emissions, no need for fuel, and the potential for installation in a wide range of locations with access to sunlight. In this investigation, heterocyclic derivatives were synthesized from several porphyrin derivatives (4,4',4",4"'-(porphyrin-5,10,15,20-tetrayl) tetra benzoic acid) compound (3), obtained by reaction Pyrrole with 4-formyl benzoic acid. Subsequently, porphyrin derivative-component amides 5a, 5b, and 5c were produced by reacting compound (3) with amine derivatives at a 1:4 molar ratio. These derivatives exhibited varying sensitivities for utilization in solar cells, with compound 5a displaying the highest power conversion efficiency (PCE) at 1.37%, as determined by measuring the short circuit current (Jsc), open-circuit voltage (Voc), and fill factor (FF) (Jsc = 2.24 mA cm-2, Voc = 0.80 mV, FF = 76.5%). Meanwhile, compound 5c exhibited the lowest PCE at 0.94% (Jsc = 1.55 mA cm-2, Voc = 0.750 mV, FF = 76.4%).